Filosofi Penataan Ruang Spasial Vertikal Pada Rumah Tradisional Saoraja Lapinceng Kabupaten Barru - Wasilah Wasilah; A. Hildayanti (RUAS (Review of Urbanism and Architectural Studies), 2016)
Bugis vertically traditional house is generally divided into three parts: head, body and leg home. The third part has a function and a different philosophy but as one that in synergy. In the field of architectural, philosophy plays a decisive role in the spatial distribution of building space. Mainly in traditional buildings such as Saoraja Lapinceng in Barru which has a variety of philosophical and meaningful messages resulting from the interpretation of the community against natural phenomena and customs that developed in the area. But in the days of modernization, most people do not know the philosophy applied to Saoraja Lapinceng. Therefore, this descriptive study will identify various philosophies contained in each division of the spatial space vertically on Saoraja Lapinceng. Through analysis techniques diachronic reading is a search method traces the history and ideology prevailing in Barru, it is known that the Bugis Barru divide the space vertically into three parts, namely "rakkeang" or the top of the house serves as a place to stay occupant of women symbolizing the group elevated, "ale bola" or the middle part serves as a male occupant symbolize authority and in controler, and "awa bola" or bottom serves as a storage area residents working equipment symbolizes foot and driving.Keywords: Bugis, philosophy of space, vertical spatial space, traditional home